The role of the human Translationally Controlled Tumor Protein (TCTP) in mitosis - Buechler, Betsy Lauren, author; DeLuca, Jennifer G., author (Colorado State University. Libraries, 2009)
Mitosis is the complex process that results in division of DNA and other cellular components into two daughter cells. Successful cell division requires that microtubules of the mitotic spindle attach to the kinetochores of mitotic chromosomes. These attachments are used for both aligning chromosomes at the spindle equator and for the physical separation of sister chromosomes during anaphase. In the study of how microtubules and kinetochores work together during mitosis, researchers are searching for new proteins that may help to piece together this complex puzzle. The Translationally Controlled Tumor Protein (TCTP) has been suggested to play a role in mitotic cell division, as it has been immuno-localized to the mitotic spindle, however, its precise function in mitosis remains unknown. The goal of my project is to determine the role of human TCTP in mitosis. Thus far, my research has shown that TCTP is located at the microtubules during mitosis, and when knocked down by siRNA treatment, human HeLa H2B-GFP cells (GFP-tagged chromosomes) are either unable to complete mitosis or take an extended time to do so. Currently, I am undergoing procedures to pick the most suitable human cell line in which to study the roles of TCTP during mitosis (HeLa-S3, HeLa-Kyoto, or HeLa H2B-GFP), and a mitotic index and characterization of this cell line. In the future, I plan to look in to the association between F-actin and TCTP, recently brought to light by Bazile et al, 2009.
Keywords: microtubule; kinetochore; mitotic cell division; TCTP; translationally controlled tumor protein; mitosis